1991
DOI: 10.1111/j.1432-1033.1991.tb16283.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effects on the binding of vanadate to the sarcoplasmic reticulum calcium‐transport enzyme

Abstract: The effect which hydrostatic pressure exerts on the binding of vanadate to the calcium-transport enzyme was determined. The recent unavailability of radioactive vanadate prevented direct measurements of vanadate binding.The vanadate-free enzyme fraction was instead monitored by phosphorylating it with ATP according to Medda and Hasselbach [Medda, P. & Hasselbach, W. (1983) Eur. J . Biochem. 137, 7 -141. Vanadate binding is reduced with rising pressure at first markedly and subsequently, above 30 MPa, relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several studies have showed that prolonged treatment with vanadyl sulfate has no toxic effects (Cam et al 1993; Mongold et al 1990), whereas orthovanadate was toxic because of inhibition of growth‐factor‐induced protein synthesis (VinA als et al, 2001). Vanadate is a known inhibitor of a number of phosphatases (Nechay et al 1986) including Ca 2+ ‐ATPases (Ronzani et al 1991), CF1‐ATPase (Carmeli et al 1992), Na + /K + ‐ATPase (Cantley et al 1977), and H + /K + ‐ATPase (Dafnis et al 1992) and oral administration has a large toxic effect on the rat myocardium (Pytkowski and Jagodzinska‐Hamann 1996). The vanadyl ion is less toxic than the vanadate ion, as judged by the LD 50 values in several animals (Llobet and Domingo 1984; Waters 1977), and the vanadyl state is likely the therapeutically active form of vanadium in cells (Nakai et al 1995; Sakurai et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have showed that prolonged treatment with vanadyl sulfate has no toxic effects (Cam et al 1993; Mongold et al 1990), whereas orthovanadate was toxic because of inhibition of growth‐factor‐induced protein synthesis (VinA als et al, 2001). Vanadate is a known inhibitor of a number of phosphatases (Nechay et al 1986) including Ca 2+ ‐ATPases (Ronzani et al 1991), CF1‐ATPase (Carmeli et al 1992), Na + /K + ‐ATPase (Cantley et al 1977), and H + /K + ‐ATPase (Dafnis et al 1992) and oral administration has a large toxic effect on the rat myocardium (Pytkowski and Jagodzinska‐Hamann 1996). The vanadyl ion is less toxic than the vanadate ion, as judged by the LD 50 values in several animals (Llobet and Domingo 1984; Waters 1977), and the vanadyl state is likely the therapeutically active form of vanadium in cells (Nakai et al 1995; Sakurai et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…0006-2960/93/0432-10929S04.00/0 © 1993 American Chemical Society Despite broad interest in the use of SCA, little has been done on characterization of the molecular basis of antigen binding by SCA molecules as well as on definition of thermodynamic parameters involved in this interaction. Hydrostatic pressure is now established as a valuable tool in the study of interactions between protein subunits (Paladini & Weber, 1981;Thompson & Lakowicz, 1984; Silva et al, 1986;Coelho-Sampaio et al, 1991) and between proteins and ligands (Li et al, 1976a; Masson & Balny, 1990; Ronzani et al, 1991). Using hydrostatic pressure, it is possible to derive information regarding the thermodynamics of biological processes under isothermal conditions (Weber & Drickamer, 1983;Weber, 1987Weber, , 1992.…”
mentioning
confidence: 99%